1973
DOI: 10.1042/bj1340869
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of acetamidothiazoles in the rat. 2-Acetamido-, 2-acetamido-4-methyl- and 2-acetamido-4-phenyl-thiazole

Abstract: The metabolism of some anti-inflammatory acetamidothiazoles was studied in the rat. The main metabolites were the corresponding acetylthiohydantoic acids, produced by fission of the thiazole ring. Minor metabolites arising from oxidation of the methyl or phenyl substituents were also identified. The structures of metabolites were established spectroscopically (u.v., i.r., n.m.r. and mass spectroscopy) and by identification with authentic specimens. The excretion of the original compounds and of metabolites, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The thioformamide thus formed is believed to be the proximate toxicant derived from thiabendazole [313]. Additional examples of biologically-active thiazoles that undergo ring opening (see Figure 49) include the immunomodulatory agent SM-8849 [314], the NSAID sudoxicam [315], anti-inflammatory 2-acetylaminothiazoles [316] and the hepatoprotective agent YH-439 [317]. The NSAID sudoxicam has been withdrawn from the market due to hepatotoxic consequences, a phenomenon that has been linked to the thiazole ring scission observed during the metabolism of this compound.…”
Section: Occurrence and Frequencymentioning
confidence: 99%
“…The thioformamide thus formed is believed to be the proximate toxicant derived from thiabendazole [313]. Additional examples of biologically-active thiazoles that undergo ring opening (see Figure 49) include the immunomodulatory agent SM-8849 [314], the NSAID sudoxicam [315], anti-inflammatory 2-acetylaminothiazoles [316] and the hepatoprotective agent YH-439 [317]. The NSAID sudoxicam has been withdrawn from the market due to hepatotoxic consequences, a phenomenon that has been linked to the thiazole ring scission observed during the metabolism of this compound.…”
Section: Occurrence and Frequencymentioning
confidence: 99%
“…In the preceding paper we described studies on the metabolism and excretion, by the rat, of some 4substituted 2-acetamidothiazoles (Chatfield & Hunter, 1973). These compounds were part of a series of anti-inflammatory compounds (Evans, 1972) of which the most active member was the 4-chloromethyl compound (I).…”
mentioning
confidence: 99%
“…Mizutani (1993Mizutani ( , 1994 and Mizutani and Suzuki (1996) reported that epoxidation of the C4-C5 double bond and subsequent ring scission of substituted thiazoles results in the formation of the corresponding -dicarbonyl metabolites and thioamide derivatives. Similar thiazole ring scission has also been observed in metabolism studies with the immunomodulatory agent SM-8849 (Yabuki et al 1997) and anti-inflammatory 2-acetylaminothiazoles (Chatfield and Hunter 1973). The hepatoprotective agent YH-439 (Yoon et al 1998) undergoes thiazole hydroxylation at the C5 position by cytochrome P450, followed by thiazole ring opening between the sulfur and the C5 by esterases, forming metabolites containing carbonthionyl and the acid.…”
Section: Discussionmentioning
confidence: 80%